If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + x = 4(x + -3) + 6 Reorder the terms: 2 + 3x + x = 4(x + -3) + 6 Combine like terms: 3x + x = 4x 2 + 4x = 4(x + -3) + 6 Reorder the terms: 2 + 4x = 4(-3 + x) + 6 2 + 4x = (-3 * 4 + x * 4) + 6 2 + 4x = (-12 + 4x) + 6 Reorder the terms: 2 + 4x = -12 + 6 + 4x Combine like terms: -12 + 6 = -6 2 + 4x = -6 + 4x Add '-4x' to each side of the equation. 2 + 4x + -4x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + 0 = -6 + 4x + -4x 2 = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 2 = -6 + 0 2 = -6 Solving 2 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 49x^2=37x-35 | | 2*x^2-3*x-15=5 | | X+y=24x^2+y^2=306 | | -18=2x-4 | | 2(4x^2-5)-[4(4x^2-1)+6]= | | 8-x=2x+14 | | F(x)=-2x^3-3 | | x*5=6000 | | (X+15)+20=90 | | 4x^2-4x-12=0 | | x*5=600000 | | 12(x+15)=13x+2 | | xe(xy)dy+ye(xy)dy=0 | | x*Y=600000 | | 4m=17m | | G(x)=-3x-3 | | x+5=6000 | | Y=2x^3-3x^2+x-6 | | -3+5v=-38 | | -2b-6+3b-2= | | 2.4c+6= | | 40+5x=5.00 | | Y=10x^3+7x^2+16x+3 | | 4(y-3)-6y=-26 | | 2x-6+108=180 | | 121k^2-36=0 | | 34=2x+10 | | 2x-7=3 | | -27x^3+8x=0 | | 0=x^2+16x-22 | | z+10+3x+30=180 | | 7+nx-6=31 |